2018
DOI: 10.1787/2f391534-en
|View full text |Cite
|
Sign up to set email alerts
|

The 2030 Agenda and Development Co-operation Results

Abstract: This paper is published under the responsibility of the Secretary-General of the OECD. The opinions expressed and the arguments employed herein do not necessarily reflect the official views of OECD countries. The publication of this document has been authorised by Brenda Killen, Deputy Director of the OECD Development Cooperation Directorate. This document and any map included herein are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…To be more precise, future research on social mentality to assist health could tend to explore diversified methods to cultivate a healthy social mentality from the perspective of art, improving the SPPS, strengthening the refinement of population research and the comparative study of populations, and exploring the influencing factors and cultivation methods of a healthy social mentality from the perspective of methodology. Furthermore, it is an important topic to explore new training methods for healthy social mentality in the future, which assist the achievement of SDG 3, ensuring healthy lives and promoting well-being for all at all ages, and SDG 11, building sustainable cities and communities [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To be more precise, future research on social mentality to assist health could tend to explore diversified methods to cultivate a healthy social mentality from the perspective of art, improving the SPPS, strengthening the refinement of population research and the comparative study of populations, and exploring the influencing factors and cultivation methods of a healthy social mentality from the perspective of methodology. Furthermore, it is an important topic to explore new training methods for healthy social mentality in the future, which assist the achievement of SDG 3, ensuring healthy lives and promoting well-being for all at all ages, and SDG 11, building sustainable cities and communities [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, sustainable mental health at the individual level can form a healthy social mentality [ 4 ] and the public’s attitude toward COVID-19 reflects a nation’s culture, quality, and competitiveness, in which a healthy social mentality is conducive to dealing with the current and post-COVID-19 situations [ 5 ]. Harmonious societies can be achieved and supported by a healthy social mentality [ 6 ], which facilitates sustainable cities and communities in line with the United Nations SDG 11 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bendixen (2001, p. 13), looking for links and relations between market-driven economies and culture, concluded that modern economies could not develop without the contribution of culture. On the other hand, the great importance of culture for the economy and societies (Engberg-Pedersen, & Zwart, 2018;Fukuyama, 2003;Sanetra-Szeliga, 2018, pp. 50-58), especially local (Kurowska-Pysz, 2014, p. 43) justifies analysing costs and institutions in general.…”
Section: Literature Reviewmentioning
confidence: 99%